« Respectabilité anti-système » et complot américano-sioniste - Nelly Quemener (Communication)
In today’s world, conspiracy culture is regularly actualized, fomented by a powerful few. Social networks and digital platforms such as YouTube give that culture room to grow and organize, in spaces such as that analyzed by the author: the comments section of Dieudonné’s YouTube channel. Positing these comments as chain reactions that produce intensification phenomena, this article examines the processes and conditions whereby interpretations of current events and history that draw on historical negationism and the American Zionist conspiracy occur, are shared, and acquire a kind of “anti‑system respectability.”